Aesthetic smile component before and after extraction and non-extraction orthodontic treatment in Class I Angle malocclusion patient - Winoto, Ervina Restiwulan; Alfiandini, Ratna Nurlia; Fahrial, Selvina Alisandra (Indonesian Journal of Dental Medicine, 2025)
Background: Approximately 80% of Indonesians suffer from malocclusion, a disease related to oral health issues. Orthodontic treatment, whether extraction or non-extraction, enhances the smile's aesthetics and stomatognathic function. To guarantee a result that is both practical and aesthetically pleasing, treatment selection necessitates thorough investigation. Purpose: the aim of this study is to compare the appearance of smiles in class I Angle type 1 malocclusions before and after orthodontic treatment. Methods: This study is an analytical retrospective study using frontal photos and a sample of medical records of orthodontic patients who finished orthodontic treatment at the Dental Hospital/Rumah Sakit Gigi dan Mulut Pendidikan (RSGMP), Universitas Airlangga (UNAIR), between 2017 and 2024. There were 46 non-extraction cases and 37 extraction cases. Result: Following premolar extraction, the buccal corridor increased by 3.11% ± 7.33% (p < 0.05) and the smile width by 1.49% ± 4.43%. Only grin breadth increased significantly (1.64% ± 4.23%) in the non-extraction group. There were no discernible differences between the extraction and non-extraction groups in Class I Angle malocclusion patients, according to the independent t-test findings. Conclusion: The extraction and non-extraction groups' average smile aesthetics scores before and after treatment do not differ significantly in Class I Angle malocclusion patients at RSGMP UNAIR.